Myogenin level tends to decrease in adult male cigarette smokers - Ihim, Augustine Chinedu; Manafa, Patrick O.; Ekechukwu, Vincent T.; Vera, Manafa I.; Chukwudi, Victor N.; Ogbuowelu, Sabina O. (Faculty of Medicine, Universitas Trisakti, 2020)
BackgroundThe World Health Organization has warned that cigarette smoking is an avoidable risk factor for endothelial injury. Myogenin might play a role in muscle metabolism and energy utilization. Electrolytes and minerals are involved in most cellular activities. The objective of this study was to compare myogenin and electrolyte levels between adult male cigarette smokers (CS) and non-smokers (NS). MethodsA cross-sectional study was conducted involving 90 subjects, consisting of 55 CS and 35 NS. The sandwich enzyme-linked immunosorbent assay was used to determine myogenin levels while the ion-selective electrode method was used to determine electrolyte levels. The levels of sodium, potassium, and chloride and the body mass index (BMI) were measured. Mann-Whitney and independent t-test were used to analyse the data. Results The BMI of CS was significantly lower than that of NS (p < 0.05). The mean serum levels of sodium (145.23 ± 1.87), potassium (4.00 ± 0.31) and chloride (103.95 ± 1.60) were significantly higher in the CS than in the NS (these being 142.38 ± 2.49, 3.83 ± 0.33, and 101.48 ± 2.08, respectively) (p<0.05). Myogenin levels (44.24 ± 14.60 pg/mL) tended to decrease in the CS group compared to the NS group (59.66 ± 61.73 pg/mL), but the difference was statistically not significant (p=0.769).Conclusion The study demonstrated that higher concentrations of sodium, potassium and chloride with lower concentrations of myogenin in smokers may be associated with higher risk of skeletal muscle tissue injury probably due to the inability of the affected small blood vessels to transport electrolytes to tissues.